Clinical evaluation of an application aid for less-invasive surfactant administration (LISA). Issue 2 (6th October 2020) - Maiwald, Christian Achim; Neuberger, Patrick; Franz, Axel R; Engel, Corinna; Vochem, Matthias; Poets, Christian F
Abstract : Background: Less-invasive surfactant administration (LISA) is increasingly used. We investigated the feasibility of a new LISA-device (Neofact®) in neonates. Design: Prospective observational pilot study with open-label LISA in two tertiary neonatal intensive care units. Patients: 20 infants with a gestational age of ≥26+0/7 weeks and an indication for LISA (Respiratory Severity Score (RSS)≥5 or fraction of inspired oxygen (FiO2 ) ≥0.30). Infants with respiratory tract malformations or unavailability of an instructed neonatologist were excluded. Main outcome measures: Success of LISA, defined as laryngoscopy-confirmed intratracheal catheter position or a decrease in FiO2 by ≥0.05 or to 0.21, accompanied by an RSS decrease of ≥2; number of attempts needed for tracheal catheterisation. Results: 20/57 screened infants were enrolled. Successful application occurred in 19/20 (95%). One application failed after three attempts. No device-related adverse events occurred. The median number of attempts was 2, success rate per attempt 19/31 (61%). Conclusion: LISA via Neofact® appears feasible. Abstract : This paper reports on a new medical device to administer surfanctant (LISA technique), including a useful video on the tool.